Formation and Geometrical Control of Polygon‐Like Metal‐Coordination Assemblies. Issue 35 (12th July 2013) - Maeda, Hiromitsu; Akuta, Ryo; Bando, Yuya; Takaishi, Kazuto; Uchiyama, Masanobu; Muranaka, Atsuya; Tohnai, Norimitsu; Seki, Shu
Abstract Polygon‐like [2+2]‐ and [3+3]‐type metal complexes were prepared from dipyrrin dimers connected by acute‐angled spacers. The electrical conduction depends strongly on the packing alignment of the compounds, revealing the presence of effective hopping pathways for holes with relatively high mobility up to 0.11 cm2 V−1 s−1 along the aligned axis of [3+3]‐type metal‐bridged assemblies. These observations correlated with the geometrical control of the π‐conjugated metal complexes in the cyclic structures, which enables their ordered arrangement in the assemblies.